Analisis Yuridis Implementasi Pasal 54 UU Nomor 35 Tahun 2009 dalam Mengatasi Overkapasitas Lembaga Pemasyarakatan - Ahyar P; Rachmad Julian Nasution; Annisa Putri; Zahra Safira Sirait (Darul Yasin Al Sys, 2026)
The implementation of Article 54 of Law Number 35 of 2009 on Narcotics remains suboptimal because imprisonment continues to dominate the handling of persons who abuse narcotics and contributes to worsening prison overcrowding in Indonesia. This study aims to analyze the regulation of rehabilitation for narcotics addicts and victims of narcotics abuse, examine its implementation in criminal justice practice, and assess the effectiveness of rehabilitation as a solution to prison overcrowding. The study employed a normative legal method using statutory, conceptual, and case approaches. Primary, secondary, and tertiary legal materials were collected through a literature review and subsequently analyzed using qualitative descriptive analysis with deductive reasoning. The findings indicate that Article 54 of Law Number 35 of 2009 normatively mandates medical and social rehabilitation for narcotics addicts and victims of narcotics abuse as a health- and recovery-oriented approach. However, its implementation remains constrained by the dominance of repressive approaches in law enforcement, limited rehabilitation facilities, the suboptimal functioning of the Tim Asesmen Terpadu, and disparities in judicial decisions. These obstacles result in many persons who abuse narcotics continuing to receive prison sentences, thereby contributing to increased prison overcrowding. Based on the theories of legal effectiveness and modern sentencing, the consistent implementation of rehabilitation can reduce the number of narcotics-related prisoners while shifting the orientation of treatment from punishment to recovery. This study affirms that optimizing Article 54 through strengthened integrated assessments, the equitable distribution of rehabilitation facilities, and consistency among law enforcement officials constitutes a strategic measure for establishing a more humane, effective, and equitable criminal justice system.